Mapear a mobilidade, a partir de Gonça, Guimarães - Beatriz Ferreira Merouço (2020)
This thesis focuses on a small, low density, urban agglomeration, in order to raise a broader reflection on mobility as an essential dimension of the territory and the urbanization processes of an hyperactive society. This small settlement makes up a civil parish on the edge of Guimarães which borders with Braga to the north and with Fafe to the west. Here the urban network is fragmented and stands out from the continuous and scattered urban patchwork that covers the southwest area of the municipality and extends through the Ave Valley to the municipalities of Vila Nova de Famalicão, Santo Tirso and Trofa. Here the discussion on territory tries to steer away from a purely technocratic point of view and makes a claim for architecture as a political project. One that is able to escape from immediate solutions, disconnected from and unconscious of the idea of society that takes shape through form. In this study, an understanding on mobility and, consequently, on territory is developed from an interview with three Gonça residents. Although the spoken word is captured and interpreted with the help of established concepts, here the inhabitants take on the role of primary source of study for the use of the territory or, in other words, for the play of movements and stays within it. This study does not limit itself to written reflection, it also involves the desire to enrich these reflections through the means of drawing.